Comprehensive Update on Rabies: A Neglected Zoonotic Disease of Public Health Concern - Kavitha Guladahalli Manjunatha; Chethana Chandrahasa; Sadanand Dangari Akshay; Akhila Dharnappa Sannejal; Rajeshwari Vittal; Govindaiah Kavitha; Khang Wen Goh; Shrikrishna Isloor; Devananda Devegowda (Progress in Microbes and Molecular Biology)
Rabies, a deadly viral zoonosis, that has driven mankind for centuries continues to be a major global public health threat, primarily affecting under developed areas. The virus targets the central nervous system of warm-blooded animals and claims the lives of over 60,000 individuals annually. Often categorized as a "neglected" disease, zoonoses constitute the majority of emerging infectious ailments.  India carries the greatest share of worldwide mortalities resulting from rabies transmitted by dogs to humans. Despite this, rabies is not definable in India, and it continues to be denied adequate consideration when it comes to public health issues.  Dogs serve as the primary reservoirs for the rabies virus, transmitting it through direct contact with their saliva including bites, scratches, and exposure to broken skin and mucous membranes. Despite, the fact that the cure for rabies remains elusive, it is possible to prevent this fatal disease through proper pre- and post-exposure prophylaxis and early laboratory diagnosis.  Diagnostic technologies like RT PCR, qPCR, dRIT, dFAT, and LFA are highly sensitive and specific in the rapid detection of rabies virus and play a crucial role in preventing the disease. Furthermore, vaccination both, pre- and post-exposure prophylaxis, coupled with increased public awareness, can significantly mitigate the impact of health concerns at the community level. Hence this comprehensive review emphasizes its transmission dynamics, diagnostic techniques, and preventive strategies aiming to raise awareness and enhance efforts to combat this neglected zoonotic disease.